(untitled) (Marketing Journal, 2026)
This article analyzes the role of global agri -food markets in the global economy and their development trends influenced by population growth, urbanization, and changes in consumption patterns. The study examines the growth dynamics of agricultural and org anic product markets, as well as the impact of digital transformation, artificial intelligence, IoT, and "precision farming" technologies on production efficiency. The article analyzes the production and export potential of Uzbekistanʼs agro - food sector, priority areas in fruit and vegetable cultivation, and existing problems in processing, storage, and logistics infrastructure. It also substantiates the main strateg ic tasks and promising directions aimed at increasing the competitiveness of the countryʼs agro-food market by 2030. This will be achieved through adaptation to international market requirements, expansion of the value chain, and ensuring sustainable development.